1993
DOI: 10.1111/j.1365-2265.1993.tb02406.x
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term follow‐up study of patients with non‐toxic diffuse goitre in Japan

Abstract: Summary OBJECTIVE Although non‐toxic diffuse goitre is a common disorder, little is known of the clinical course of patients. We therefore decided to investigate the long‐term clinical outcome of patients with non‐toxic diffuse goitre. DESIGN A retrospective study. PATIENTS Of 850 patients with non‐toxic diffuse goitre who met our criteria and were seen in our thyroid clinic between 1977 and 1985, 108 who had been followed for from 5 to 14 years (mean 8 years) were entered in this study. All patients fulfilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In a twenty-year follow-up of a sample of a south-western United States population aged 11-18 years, spontaneous regression by the age of 30 years occurred in 60% of subjects who initially had diffuse goitres (Rallison et al, 1991). In contrast, a retrospective study of a selected clinic population in Japan, found that diffuse goitres disappeared in only 5% of a subsample of 108 subjects after eight years of follow-up, and 7% of these subjects with goitre developed thyroid dysfunction (Hara et al, 1993). The current study has shown that the presence of a 'simple' goitre is not predictive of any biochemical or clinical evidence of thyroid dysfunction over twenty years.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a twenty-year follow-up of a sample of a south-western United States population aged 11-18 years, spontaneous regression by the age of 30 years occurred in 60% of subjects who initially had diffuse goitres (Rallison et al, 1991). In contrast, a retrospective study of a selected clinic population in Japan, found that diffuse goitres disappeared in only 5% of a subsample of 108 subjects after eight years of follow-up, and 7% of these subjects with goitre developed thyroid dysfunction (Hara et al, 1993). The current study has shown that the presence of a 'simple' goitre is not predictive of any biochemical or clinical evidence of thyroid dysfunction over twenty years.…”
Section: Discussionmentioning
confidence: 91%
“…In other shorter longitudinal studies, one-third of subjects initially anti-thyroid antibody positive in a population survey no longer had detectable antibodies 6 years later (Hawkins et al, 1980), whereas a five-year follow-up study of a sample of healthy elderly people aged over 70 years found that, despite significant fluctuations in antibody titre, all 51 subjects who were originally anti-thyroid antibody positive remained positive at follow-up (Lazarus et al, 1984). Incidence rates for hyperthyroidism in the community from large population studies average 0*1/1000/year in men and 0.4/1000( year in women, but the age-specific incidence varies considerably (Furszyfer ef al., 1970;Mogensen & Green, 1980;Barker & Phillips, 1984;Haraldsson et al, 1985;Berglund et al, 1990). The peak age-specific incidence of Graves' disease was between 20 and 49 years in two studies (Furszyfer et al, 1970;Mogensen & Green, 1980), but increased with age in Iceland (Haraldsson et al, 1985) and peaked at 60-69 years in Malmo (Berglund et al, 1990).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation